Fixed-time disturbance observer-based robust fault-tolerant tracking control for uncertain quadrotor UAV subject to input delay - Liu, Kang; Wang, Rujing; Zheng, Shijian; Dong, Shifeng; Sun, Guowei (Nonlinear dynamics, 2022)
This study focuses on the design of a fixed-time disturbance observer-based robust fault-tolerant tracking control scheme for an uncertain quadrotor unmanned aerial vehicle (UAV), which allows the quadrotor UAV to track a presupposed trajectory despite the simultaneous existence of model uncertainties, external disturbances, actuator faults, and input delay. First of all, the combination of Pade approximation and an intermediate variable is employed to reduce the complexity of studying the quadrotor system with input delay. Secondly, the fixed-time disturbance observer is proposed to eliminate the effects of the composite disturbances without requiring some serious assumptions. Subsequently, the new nonsingular fixed-time sliding mode manifold and the auxiliary system are developed to overcome the singular problem without any piecewise continuous functions. In the sense of the Lyapunov theorem, it is proved that the tracking errors of the closed-loop system converge to the origin within a fixed time regardless of the initial conditions. Eventually, extensive comparative simulations are performed to manifest the feasibility and validity of the proposed control strategy in terms of disturbance rejection, fault-tolerance, chattering elimination, and singularity-free.